filmov
tv
If x=cy+bz,y=az+cx,z=bx+cy, then prove that x^2/(1-a^2)=y^2/(1-b^2)=z^2/(1-c^2)
Показать описание
Dr. Debprasad Majumder
similar sum
Mathematics for Mankind- online class
If x=cy bz
y=az cx
z=bx cy
then prove that x^2/(1-a^2)=y^2/(1-b^2)=z^2/(1-c^2) x^2/(1-a^2)=y^2/(1-b^2)=z^2/(1-c^2) x=cy bz
y=az cx
Рекомендации по теме
0:06:21
If x=cy+bz,y=az+cx,z=bx+cy, then prove that a^2+b^2+c^2+2abc=1
0:07:39
If x=cy+bz,y=az+cx,z=bx+cy, then prove that x^2/(1-a^2)=y^2/(1-b^2)=z^2/(1-c^2)
0:06:00
If x=cy+bz,y=az+cx,z=bx+ay then prove that, x^2/1-a^2=y^2/1-b^2 #X #DpmSir
0:05:29
x=cy+bz, y=az+cx, z=bx+ay then prove that x^2 : y^2 = 1 - a^2 : 1 - b^2
0:03:36
If `x = cy + bz, y = az + cx , z =bx + ay,` then prove that `x^2/(1-a^2)= y^2/(1-b^2)`
0:02:30
If `x@ + y^2 + z^2!=0, x=cy + bz, y = az + cx`, and `z = bx + ay`, then `a^2 + b^2 + c^2 + 2ab
0:08:32
If, x=cy+bz,y=az+cx,z=bx+ay; then prove that x^2:y^2=1-a^2:1-b^2
0:03:02
Given x=cy+bz,y=az+cx and z=bx+ay, then prove `a^(2) +b^(2) +c^(2) `+2abc =1.
0:11:06
If x=cy+bz, y=az+cx, z=bx+ay, then prove that x²/1-a²=y²/1-b²=z²/1-c²
0:08:03
If, bz+cy/a=cx+az/b=ay+bx/cThen prove that x/a(b^2+c^2-a^2)=y/b(c^2+a^2-b^2)=z/c(a^2+b^2-c^2)
0:03:43
Given, x=c y+b z, y=a z+c x, z=b x+a y, where x, y, z are not all zero, prove that a^2+b^2+c^2+2 ...
0:04:07
If `(ay-bx)/c = (cx - az)/b = (bz - cy)/a , ' then prove that ' x/a = y/b = z/c `.
0:05:31
If x=cy+bz, y=az+cx, z=bx+ay where x,y,z are not all zeros, then find the value of a^2+b^2+c^2+2abc
0:05:18
(ay-bx)/c=(cx-az)/b=(bz-cy)/a || prove that x/a=y/b=z/c || doubt shared by Rahul kumar
0:03:47
If `x, y, z` are not all zero & if `ax + by + cz=0, bx+ cy + az=0 & cx + ay + bz = 0`, the...
0:03:29
Given planes `P_1:cy+bz=x` `P_2:az+cx=y` `P_3:bx+ay=z` `P_1, P_2 and P_3
0:14:28
If bz+cy/b-c=cx+az/c-a=ay+bx/a-b then (a+b+c)(x+y+z)=ax+by+cz
0:06:41
If \( a x+c y+b z=X, c x+b y+a z=Y, b x+a y+c z=Z \) show that \( \...
0:10:31
if bz-cy/b-c=cx-az/c-a then prove that value of each ratio ay-cx/a-b # X #DpmSir
0:01:52
If x(b-c)+y(c-a)+z(a-b)=0 then show that (bz-cy)/(b-c)=(cz-az)/(c-a)=(ay-bx)/(a-b).
0:03:03
If `x = cy + bz, y = cx + az, z = bx + ay`, the value of `a² + b^2 + c^2 - 1` is
0:03:12
If planes ` x- cy - bz =0 , cx-y+az =0 and bx + ay - z=0` pass through a staight line the
0:03:46
If `x^2+y^2+z^2 ne0, x=cy+bz,y=az+cxandz=bx+ay' then 'a^2+b^2+c^2+2abc=`
0:03:31
If the planes `x-cy-bz=0, cx-y+az=0 and bx+ay-z=0` pass through a line, then the value of `a^2+b^2+